End group functionalization of poly(ethylene glycol) with phenolphthalein: towards star-shaped polymers based on supramolecular interactions - Fleischmann, Carolin; Wöhlk, Hendrik; Ritter, Helmut (Beilstein Journal of Organic Chemistry, 2014)
The synthesis of a new phenolphthalein azide derivative, which can be easily utilized in polymer analogous reactions, is presented. The subsequent cycloaddition reaction with propargyl-functionalized methoxypoly(ethylene glycol) yielded polymers bearing phenolphthalein as the covalently attached end group. In presence of per-β-cyclodextrin-dipentaerythritol, the formation of stable inclusion complexes was observed, representing an interesting approach towards the formation of star shaped polymers. The decolorization of a basic polymer solution caused by the complexation was of great advantage since this behavior enabled following the complex formation by UV–vis spectroscopy and even the naked eye.
Keywords: cyclodextrin; phenolphthalein; poly(ethylene glycol); supramolecular assembly; UV–vis spectroscopy